Draft law that regulates the decriminalization of the voluntary interruption of pregnancy in three grounds: Critical analysis - Cozzi Elzo, Ruggero; Aguilera Medina, Cristóbal (Derecho Público Iberoamericano, 2016)
The authors examine four aspects of the legislative proposal being discussed by the Chilean Congress. First, they contextualize the debate by showing the facts of the social reality in which it is being held (empirical data on why Chilean women undergo abortions), the sanitary conditions that currently exist (how the procedure is performed under prohibition conditions and its consequences on women’s health) and the data on criminalization (statistics of actual convictions and effective penalties). Second, the authors undertake a brief analysis of the three causes for abortion that the proposal seeks to legalize, highlighting the most evident ontradictions arising thereof. Third, the authors summarize the controlling rules of international human rights law applicable to the matter. Finally, the authors highlight the criminal impunity that will arise as a consequence of the enactment of the proposal, which will lead to a de facto legalization of all forms of abortion.